PROMOVENDO A SAÚDE MENTAL NA ESCOLA: ESTRATÉGIAS E INTERVENÇÕES PARA O BEM-ESTAR DOS ESTUDANTES (REMUNOM, 2023)
The mental health of students is an increasingly relevant concern in the educational context. The understanding that mental health plays a key role in students' well-being, academic performance, and social-emotional development has led to a growing demand for effective strategies and interventions to promote mental health in schools. However, despite the recognition of the importance of mental health in school, there are still challenges to overcome. The lack of financial resources, the lack of adequate training of educators and the stigma associated with mental health are just some of the obstacles faced by educational institutions. Given this panorama, this article aims to discuss strategies and interventions to promote mental health at school, focusing on the well-being of students. By promoting mental health in school, we are empowering students to cope with life's challenges, develop social-emotional skills, build healthy relationships, and seek support when needed. We are creating a welcoming and inclusive environment where mental health is valued and cared for. In this regard, it is critical that educators, mental health professionals, and policymakers work together to ensure that mental health-promoting strategies and interventions are implemented effectively and sustainably. Only through an integrated and collaborative approach can we build healthy minds and provide students with the best conditions for their success and well-being.   Key words: Education; Mental health; School.